Biparatopic nanobodies protect mice from lethal challenge with SARS‐CoV‐2 variants of concern. (20th December 2021) - Wagner, Teresa R; Schnepf, Daniel; Beer, Julius; Ruetalo, Natalia; Klingel, Karin; Kaiser, Philipp D; Junker, Daniel; Sauter, Martina; Traenkle, Bjoern; Frecot, Desiree I; Becker, Matthias; Schneiderhan‐Marra, Nicole; et al.
Abstract: The ongoing COVID‐19 pandemic and the emergence of new SARS‐CoV‐2 variants of concern (VOCs) requires continued development of effective therapeutics. Recently, we identified high‐affinity neutralizing nanobodies (Nbs) specific for the receptor‐binding domain (RBD) of SARS‐CoV‐2. Taking advantage of detailed epitope mapping, we generate two biparatopic Nbs (bipNbs) targeting a conserved epitope outside and two different epitopes inside the RBD:ACE2 interface. Both bipNbs bind all currently circulating VOCs with high affinities and are capable to neutralize cellular infection with VOC B.1.351 (Beta) and B.1.617.2 (Delta) in vitro . To assess if the bipNbs NM1267 and NM1268 confer protection against SARS‐CoV‐2 infection in vivo, human ACE2 transgenic mice are treated intranasally before infection with a lethal dose of SARS‐CoV‐2 B.1, B.1.351 (Beta) or B.1.617.2 (Delta). Nb‐treated mice show significantly reduced disease progression and increased survival rates. Histopathological analyses further reveal a drastically reduced viral load and inflammatory response in lungs. These data suggest that both bipNbs are broadly active against a variety of emerging SARS‐CoV‐2 VOCs and represent easily applicable drug candidates. Synopsis: This study reports on two highly efficient RBD‐specific biparatopic nanobodies that bind and neutralize SARS‐CoV‐2 and its currently circulating variants of concern in vitro and in vivo, underscoring the potential of nanobodies to prevent or treat SARS‐CoV‐2 infection. SARS‐CoV‐2 specific nanobodies (Nbs) binding conserved epitopes outside and two different epitopes inside the RBD:ACE2 interface form the biparatopic (bip) Nbs NM1267 and NM1268. Both bipNbs exhibit thermal stability, bind all currently circulating variants of concern with picomolar affinity and neutralize cellular infection of patient isolates of B.1.351 (Beta) and B.1.617.2 (Delta). In vivo, prophylactic treatment with NM1267 and NM1268 show significantly reduced disease progression and increased survival rates. This study demonstrates how rational design based on detailed knowledge of binding properties lead to the development of easily applicable drug candidates. Abstract : This study reports on two highly efficient RBD‐specific biparatopic nanobodies that bind and neutralize SARS‐CoV‐2 and its currently circulating variants of concern in vitro and in vivo, underscoring the potential of nanobodies to prevent or treat SARS‐CoV‐2 infection.